The Combination of Astragalus membranaceus and Angelica sinensis Inhibits Lung Cancer and Cachexia through Its Immunomodulatory Function. (3rd November 2019) - Wu, Tsung-Han; Yeh, Kun-Yun; Wang, Chen-Hsu; Wang, Hang; Li, Tsung-Lin; Chan, Yi-Lin; Wu, Chang-Jer
Abstract : Lung cancer and its related cachexia are the leading cause of cancer death in the world. In this study, we report the inhibitory effect of the combined therapy of Astragalus membranaceus and Angelica sinensis, on tumor growth and cachexia in tumor-bearing mice. Lewis lung carcinoma cells were inoculated into male C57BL/6 and CAnN.Cg-Foxn1 nu nude mice. After tumor inoculation, mice were fed orally by the combination of AM and AS in different doses. In C57BL/6 mice, the combination of AM and AS significantly inhibited the growth of cancer tumor and prevented the loss of body weight and skeletal muscle. It also diminished the formation of free radicals and cytokines, stimulated the differentiation of NK and Tc cells, and rebalanced the ratios of Th/Tc cells, Th1/Th2 cytokines, and M1/M2 tumor-associated macrophages. The herbal combination also downregulated the expression of NF κ Β, STAT3, HIF-1 α, and VEGF in tumors. In contrast, the findings were not observed in the nude mice. Therefore, the combination of AM and AS is confirmed to inhibit the progression of lung cancer, cancer cachexia, and cancer inflammation through the immunomodulatory function.